Evaluating the Role of Point-of-Care Ultrasound in Central Venous Pressure Monitoring for Critically Ill Patients. A Comprehensive Systematic Review and Meta-analysis - Eman E. Shaban (17337676) (2025)
Central venous pressure (CVP) is a critical parameter for assessing volume status in critically ill patients, traditionally measured through invasive central venous catheterization. While effective, this method poses risks such as infection and procedural complications. Point-of-care ultrasound (POCUS) has emerged as a promising, non-invasive alternative, yet its accuracy in estimating CVP remains debated. From inception to December 2024, PubMed, Embase, MEDLINE, Web of Science, and Google Scholar databases were extensively searched. The search strategy used to identify relevant studies from these databases involved combining keywords such as “Point-of-care ultrasound,” “central venous pressure,” and “critically ill” with Boolean expression “AND” and “OR.” Two independent reviewers then screened all potential studies and included those reporting the accuracy of POCUS in predicting CVP and those reporting the correlation between POCUS-measured indices and invasively-measured CVP in critically ill patients. Additionally, two independent reviewers extracted the relevant data from the included studies. Statistical analyses were conducted using MedCalc and Meta-Disc software, and quality appraisal was assessed using the QUADAS-2 tool. The review included studies evaluating POCUS-derived indices from the inferior vena cava (IVC) and internal jugular vein (IJV). Overall, strong correlations were observed between POCUS measurements and CVP, with IVC parameters showing the strongest associations. IJV measurements also demonstrated moderate reliability, particularly in scenarios where IVC assessments were impractical. Sensitivity and specificity analyses indicated that POCUS-derived indices could predict CVP with variable accuracy. These findings support the use of POCUS as a practical, non-invasive tool for estimating CVP in critically ill patients. IVC measurements appear to provide the most reliable correlations, while IJV assessments serve as a useful alternative. Despite its potential, variability in study methodologies and patient factors highlights the need for further research to refine POCUS-based CVP estimation and improve clinical application. Other Information Published in: Ultrasound in Medicine & Biology License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.ultrasmedbio.2025.04.008